KEARIFAN LOKAL DAN PENERAPANNYA DI SEKOLAH - Heronimus Delu Pingge (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
Local wisdom describes how to behave and act to respond to changes that are unique in thephysical and cultural environment of the local area. The local potential in each region inIndonesia is an asset of natural, human, technological, and cultural resources that must bemaintained and developed to improve a more civilized life. In general, school learning has beenpaying less attention to this local aspect, so that the younger generation slowly starts to leavethe noble values of the local area. The purpose of this article is to outline the form of instillinglocal wisdom through education or school.